Cloning, Expression, and Chromosome Mapping of Human Galectin-7 - Peder Madsen; Hanne H. Rasmussen; Tracey Flint; Pavel Gromov; Torben A. Kruse; Bent Honoré; Henrik Vorum; Julio E. Celis (1995)
The galectins are a family of β-galactoside-binding proteins implicated in modulating cell-cell and cell-matrix interactions. Here we report the cloning and expression of a novel member of this family (galectin-7) that correspond to IEF (isoelectric focusing) 17 (12,700 Da; pI, 7.6) in the human keratinocyte protein data base, and that is strikingly down-regulated in SV40 transformed keratinocytes (K14). The cDNA was cloned from a λgt11 cDNA expression library using degenerated oligodeoxyribonucleotides back-translated from an IEF 17 peptide sequence. The protein encoded by the galectin-7 clone comigrated with IEF 17 as determined by two-dimensional (two-dimensional gel electrophoresis) analysis of proteins expressed by transiently transfected COS-1 cells, and bound lactose. Alignment of the amino acid sequences with other members of the family showed that the amino acids central to the β-galactoside interaction are conserved. Galectin-7 was partially externalized to the medium by keratinocytes although it has no typical secretion signal peptide. Immunoblotting as well as immunofluorescence analysis of human tissues with a specific galectin-7 antibody revealed a narrow distribution of the protein which was found mainly in stratified squamous epithelium. The antigen localized to basal keratinocytes, although it was also found, albeit at lower levels, in the suprabasal layers where it concentrated to areas of cell to cell contact. Both, its cellular localization as well as its striking down-regulation in K14 keratinocytes imply a role in cell-cell and/or cell-matrix interactions necessary for normal growth control. The galectin-7 gene was mapped to chromosome 19. The galectins are a family of β-galactoside-binding proteins implicated in modulating cell-cell and cell-matrix interactions. Here we report the cloning and expression of a novel member of this family (galectin-7) that correspond to IEF (isoelectric focusing) 17 (12,700 Da; pI, 7.6) in the human keratinocyte protein data base, and that is strikingly down-regulated in SV40 transformed keratinocytes (K14). The cDNA was cloned from a λgt11 cDNA expression library using degenerated oligodeoxyribonucleotides back-translated from an IEF 17 peptide sequence. The protein encoded by the galectin-7 clone comigrated with IEF 17 as determined by two-dimensional (two-dimensional gel electrophoresis) analysis of proteins expressed by transiently transfected COS-1 cells, and bound lactose. Alignment of the amino acid sequences with other members of the family showed that the amino acids central to the β-galactoside interaction are conserved. Galectin-7 was partially externalized to the medium by keratinocytes although it has no typical secretion signal peptide. Immunoblotting as well as immunofluorescence analysis of human tissues with a specific galectin-7 antibody revealed a narrow distribution of the protein which was found mainly in stratified squamous epithelium. The antigen localized to basal keratinocytes, although it was also found, albeit at lower levels, in the suprabasal layers where it concentrated to areas of cell to cell contact. Both, its cellular localization as well as its striking down-regulation in K14 keratinocytes imply a role in cell-cell and/or cell-matrix interactions necessary for normal growth control. The galectin-7 gene was mapped to chromosome 19.